The Representation of Facts through the Subjective and the Objective Dimensions of Consciousness in William Faulkner’s Novel As I Lay Dying(1930) - Brachemi,Sakina; Khalfa,Sayeh (University of Ammar Theledji -Laghouat, 2020)
Each individual has his or her perception of reality. The implication is that because each of us perceives the world through our own eyes, reality itself changes from person to person. As I Lay Dying, a novel tends to offer a glimpse of a family situation from an outsider perspective to mirror reality and what that can be considered as the reality of what happened with Bundren family members. The novel is based on objective facts that result in a multitude of subjective interpretations from different characters with various point of view. Relying on the subjective and the objective description, this piece of research aimed at the distinction between the fact and the interpretation of fact, also to predict where the subjective reality is mentioned and where the objective reality is narrated and the reader’s engagement in the narration process. It concluded that the subjective reality of facts of the Bundrens interferes with the objective interpretation of the external voices that stimulate the reader’s consciousness to associate their subjective and objective interpretation within the reading and narration process.